Insulating material for 35KV cable and preparation method thereof
By using POE as the base material in 35KV cable insulation materials, combined with the addition of modified kaolin and composite flame retardant, the problem of difficulty in taking into account multiple properties of existing materials is solved, and the electrical, flame retardant and mechanical properties are improved, meeting the high standards requirements of medium and high voltage cables.
Patent Information
- Application Number
- CN202411947911.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
Smart Images

Figure BDA0005214155280000091
Abstract
Description
Technical Field
[0001] The invention relates to an insulating material for a 35KV cable and a preparation method thereof. Background Art
[0002] In the power transmission system, cables are key components for power transmission, and their performance directly affects the stability and safety of the entire power grid. Especially for 35KV-level medium and high voltage cables, the requirements for insulation materials are particularly strict. Since these cables are usually used for power supply in urban distribution networks, industrial facilities, and large buildings, the selected insulation materials must be able to meet a series of high-performance indicators, including but not limited to electrical properties, flame retardant properties, and mechanical properties.
[0003] For a long time, in order to achieve the above high standards, researchers have been constantly exploring new insulating materials and improving the formula and production process of existing materials. However, traditional materials are often difficult to meet all these performance requirements at the same time. Therefore, the applicant provides an insulating material for 35KV cables and a preparation method thereof. Summary of the invention
[0004] The purpose of the present invention is to provide an insulating material for a 35KV cable and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.
[0005] The technical solution for achieving the purpose of the present invention is as follows: In the first aspect of the present invention, a 35KV cable insulating material is provided, wherein the raw material components, by weight, include 75 to 100 parts by weight of POE, 0 to 10 parts by weight of PE, 0 to 5 parts by weight of POE compatibilizer, 20 to 60 parts by weight of modified kaolin, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, and 40 parts by weight of compound flame retardant.
[0006] Furthermore, the modified kaolin is obtained by modifying kaolin with styreneethyltrimethoxysilane.
[0007] Furthermore, the compound flame retardant is obtained by compounding aluminum hydroxide and benzoic acid functionalized boron nitride.
[0008] Furthermore, the mass ratio of the aluminum hydroxide to the benzoic acid functionalized boron nitride is 35.5-38.5:1.5-4.5.
[0009] The second aspect of the present invention also provides a method for preparing an insulating material for a 35KV cable, comprising the following steps:
[0010] (1) 20 to 60 parts by weight of modified kaolin, 1.5 to 4.5 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate are mixed, stirred and reacted at 84 to 86° C. for 80 to 100 minutes, then poured into 1000 parts by weight of a 10% sodium acetate solution and allowed to stand at room temperature for 3.5 to 4.5 hours, followed by filtering, washing, and drying to obtain a premix;
[0011] (2) 75-100 parts by weight of POE, 0-10 parts by weight of PE, 0-5 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 35.5-38.5 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer internal mixer for 8-12 minutes, then sent to a flat plate vulcanizer for flat plate vulcanization, and then directly subjected to ultraviolet irradiation cross-linking reaction in a molten state for 13-17 minutes to prepare an insulating material for a 35KV cable.
[0012] Furthermore, the preparation steps of the modified kaolin are as follows: kaolin, styreneethyltrimethoxysilane and ethanol are mixed, ultrasonically dispersed for 25 to 35 minutes, stirred at 58 to 62° C. at a speed of 300 to 500 r / min for 3.5 to 4.5 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0013] Furthermore, the mass ratio of kaolin, styreneethyltrimethoxysilane and ethanol is 1:1.6-2:8-12.
[0014] Furthermore, the preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 8 to 12 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 1.5 to 2.5 hours to obtain a boron nitride dispersion; 0.9 to 1 parts by mass of 4-aminobenzoic acid and 0.2 to 0.3 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.5 to 0.55 parts by mass of sodium nitrite and 5.5 to 6.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 40 to 50 minutes, and then the boron nitride dispersion is added, stirred for reaction for 3.5 to 4.5 hours, followed by suction filtration, washing, and drying to obtain benzoic acid functionalized boron nitride.
[0015] Furthermore, the rheological temperature of the torque rheometer internal mixer device is 140-150° C., and the rheological speed is 40-50 rpm.
[0016] Furthermore, the plate vulcanization step is specifically as follows: firstly vulcanize at 5 MPa for 2 to 4 minutes, and then pressurize to 10 MPa for 4 to 8 minutes; wherein, the plate vulcanization temperature is 130 to 150°C.
[0017] The ultraviolet light irradiation adopts an LED ultraviolet light irradiation device with a power of 3kW.
[0018] By adopting the above technical solution, the present invention has the following beneficial effects:
[0019] (1) The 35KV cable insulation material of the present invention uses polyolefin elastomer POE as the cable insulation material base material, and adds PE, ethylene propylene rubber, modified kaolin, antioxidant, stabilizer, compound flame retardant and other materials as additives, so that the 35KV cable insulation material can have good electrical properties, flame retardant properties and mechanical properties at the same time.
[0020] (2) The cable insulation material base material of the 35KV cable insulation material of the present invention adopts POE. Compared with the traditional ethylene propylene rubber as the cable insulation material base material, POE has excellent electrical properties, tensile properties, heat resistance and extrusion processability, can meet the performance requirements of 35KV insulation, and can also significantly reduce material costs.
[0021] (3) The 35KV cable insulation material of the present invention uses modified kaolin as filler. On the one hand, the flaky crystal structure of kaolin provides excellent mechanical reinforcement, increases the tensile strength, elongation at break and wear resistance of the 35KV cable insulation material, thereby improving the mechanical stability and service life of the 35KV cable insulation material; on the other hand, the thermal stability and thermal conductivity of the modified kaolin help prevent high-temperature aging, and enhance the flame retardant properties, ensuring the safety and reliability of the 35KV cable insulation material; on the other hand, the good fluidity and dispersibility of the modified kaolin optimize the extrusion process, reduce the shear force and equipment wear in the production process, and improve the processing efficiency.
[0022] (4) The modified kaolin of the present invention is obtained by modifying kaolin with styrene ethyl trimethoxy silane, which can increase the dispersibility of kaolin in the insulating material for 35KV cables and prevent kaolin agglomeration from affecting the mechanical properties and processing properties of the insulating material for 35KV cables.
[0023] (5) The composite flame retardant of the present invention is prepared by compounding aluminum hydroxide and benzoic acid functionalized boron nitride. During combustion, sodium hydroxide is thermally decomposed to produce water vapor to absorb heat and dilute the concentration of combustible small molecule gases. The sodium hydroxide aluminum oxide protective layer can inhibit molten droplets and promote carbonization to isolate oxygen and protect the body. At the same time, the addition of benzoic acid functionalized boron nitride can form an effective insulating layer on the surface of the burning material, delaying the degradation and combustion of the insulating material for 35KV cables, thereby improving the flame retardant properties of the insulating material for 35KV cables.
[0024] (6) The present invention uses benzoic acid functionalized boron nitride, which can effectively disperse boron nitride evenly in the base material of the 35KV cable insulation material for synergistic flame retardancy with sodium hydroxide, thereby increasing the flame retardancy of the 35KV cable insulation material; at the same time, the benzoic acid on the benzoic acid functionalized boron nitride reacts with the benzene ring on the modified kaolin to form a benzophenone derivative, which subsequently absorbs ultraviolet light energy and transitions to a singlet state under the action of ultraviolet light, and then is converted into a triplet state through intersystem crossing, and then forms transient free radicals such as POE macromolecular free radicals and benzophenone derivative molecular free radicals (carbonyl radicals) by capturing hydrogen atoms on the POE molecular chain, and the carbonyl radicals on the benzophenone derivative molecule attack the auxiliary crosslinking agent TAIC The carbon-carbon double bonds on the POE molecule and the modified kaolin form allyl radicals, and the transient free radicals on the POE and TAIC molecules and the modified kaolin combine and cross-link with each other, and the cross-linking agent TAIC molecules and the modified kaolin are grafted onto the POE molecular chain to form a branched POE molecular chain, which enhances the mechanical properties of the 35KV cable insulation material. At the same time, the transient free radical sub-cross-linking on the benzophenone derivative molecule forms a by-product benzopinacol, which can capture high-energy electrons and convert the energy of high-energy electrons into atomic vibrations (electron-phonon coupling) through the keto-enol tautomerism reaction of the ester carbonyl group, thereby playing the role of a voltage stabilizer, further enhancing the electrical properties of the 35KV cable insulation material. DETAILED DESCRIPTION
[0025] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0026] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0027] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0028] The raw materials of the embodiments of the present invention and the comparative examples are as follows:
[0029] The POE has a melt index of 0.5 g / 10 min (230° C. / 2.16 kg);
[0030] The PE is low-density polyethylene with a density of 0.91 g / cm 3 ;
[0031] The POE compatibilizer is maleic anhydride grafted POE;
[0032] The ethylene content in the EPDM rubber is 72 wt% and the density is 0.86 g / cm 3 ;
[0033] The kaolin is calcined kaolin;
[0034] The white carbon black is precipitated white carbon black;
[0035] The paraffin wax is microcrystalline paraffin;
[0036] The purity content of the zinc oxide is 99.8%;
[0037] The antioxidant is antioxidant 1010;
[0038] The stabilizer is a lead salt stabilizer;
[0039] The TAIC content is 70% TAIC;
[0040] The content of DCP (dicumyl peroxide) is 99.7 wt %.
[0041] (Example 1)
[0042] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0043] (1) 20 parts by weight of modified kaolin, 1.5 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate were mixed, stirred at 84° C. and 1000 r / min for 80 min, then poured into 1000 parts by weight of 10% sodium acetate solution and allowed to stand at room temperature for 3.5 h, then filtered, washed, and dried to obtain a premix;
[0044] (2) 75 parts by weight of POE, 5 parts by weight of PE, 3 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 38.5 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer mixer for 8 minutes, wherein the rheological temperature is 140°C and the rheological speed is 40 rpm; then the mixture is fed into a flat plate vulcanizer and first vulcanized at 5 MPa for 2 minutes, then pressurized to 10 MPa for 4 minutes; wherein the plate vulcanization temperature is 130°C, and then a 3 kW LED ultraviolet light irradiation device is used to directly perform ultraviolet light irradiation cross-linking reaction for 13 minutes in a molten state to prepare an insulating material for a 35KV cable.
[0045] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:1.6:8, ultrasonically dispersed for 25 minutes, stirred at 58°C and a speed of 300 r / min for 3.5 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0046] The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 8 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 1.5 hours to obtain a boron nitride dispersion; 0.9 parts by mass of 4-aminobenzoic acid and 0.2 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.5 parts by mass of sodium nitrite and 5.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 40 minutes, and then the boron nitride dispersion is added, stirred for reaction for 3.5 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
[0047] (Example 2)
[0048] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0049] (1) 60 parts by weight of modified kaolin, 4.5 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate were mixed, stirred at 85° C. and 1000 r / min for 90 min, then poured into 1000 parts by weight of 10% sodium acetate solution and allowed to stand at room temperature for 4 h, followed by filtering, washing, and drying to obtain a premix;
[0050] (2) 85 parts by weight of POE, 10 parts by weight of PE, 5 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 35.5 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer mixer for 10 minutes, wherein the rheological temperature is 145°C and the rheological speed is 45 rpm; then the mixture is sent to a flat plate vulcanizer for continuous vulcanization at 5 MPa for 3 minutes, and then pressurized to 10 MPa for continuous vulcanization for 6 minutes; wherein the flat plate vulcanization temperature is 140°C, and then a 3kW LED ultraviolet light irradiation device is used in the molten state to directly carry out ultraviolet light irradiation cross-linking reaction for 15 minutes to prepare an insulating material for a 35KV cable.
[0051] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:1.8:10, ultrasonically dispersed for 30 minutes, stirred at 60°C and 400 r / min for 4 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0052] The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.95 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 5.55 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 45 minutes, and then the boron nitride dispersion is added, stirred for reaction for 4 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
[0053] (Example 3)
[0054] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0055] (1) 60 parts by weight of modified kaolin, 3 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate were mixed, stirred at 86° C. and 1000 r / min for 100 min, then poured into 1000 parts by weight of 10% sodium acetate solution and allowed to stand at room temperature for 4.5 h, then filtered, washed, and dried to obtain a premix;
[0056] (2) 90 parts by weight of POE, 10 parts by weight of PE, 5 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 37 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer mixer for 12 minutes, wherein the rheological temperature is 150°C and the rheological speed is 50 rpm; then the mixture is sent to a flat plate vulcanizer for continuous vulcanization at 5 MPa for 4 minutes, and then the pressure is increased to 10 MPa for continuous vulcanization for 8 minutes; wherein the flat plate vulcanization temperature is 150°C, and then a 3 kW LED ultraviolet light irradiation device is used in the molten state to directly carry out ultraviolet light irradiation cross-linking reaction for 17 minutes to prepare an insulating material for a 35KV cable.
[0057] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:2:12, ultrasonically dispersed for 35 minutes, stirred at 62° C. and a speed of 500 r / min for 4.5 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0058] The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 12 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2.5 hours to obtain a boron nitride dispersion; 1 part by mass of 4-aminobenzoic acid and 0.3 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.55 parts by mass of sodium nitrite and 6.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 50 minutes, and then the boron nitride dispersion is added, stirred for reaction for 4.5 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
[0059] (Comparative Example 1)
[0060] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0061] (1) 60 parts by weight of kaolin, 4.5 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate were mixed, stirred at 85° C. and 1000 r / min for 90 min, then poured into 1000 parts by weight of 10% sodium acetate solution and allowed to stand at room temperature for 4 h, then filtered, washed, and dried to obtain a premix;
[0062] (2) 85 parts by weight of POE, 10 parts by weight of PE, 5 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 35.5 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer mixer for 10 minutes, wherein the rheological temperature is 145°C and the rheological speed is 45 rpm; then the mixture is sent to a flat plate vulcanizer for continuous vulcanization at 5 MPa for 3 minutes, and then pressurized to 10 MPa for continuous vulcanization for 6 minutes; wherein the flat plate vulcanization temperature is 140°C, and then a 3kW LED ultraviolet light irradiation device is used in the molten state to directly carry out ultraviolet light irradiation cross-linking reaction for 15 minutes to prepare an insulating material for a 35KV cable.
[0063] The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.95 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 5.55 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 45 minutes, and then the boron nitride dispersion is added, stirred for reaction for 4 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
[0064] (Comparative Example 2)
[0065] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0066] (1) 60 parts by mass of modified kaolin, 4.5 parts by mass of boron nitride, and 22 parts by mass of boron trifluoride etherate were mixed, stirred at 85° C. and 1000 r / min for 90 min, then poured into 1000 parts by mass of 10% sodium acetate solution and allowed to stand at room temperature for 4 h, followed by filtering, washing, and drying to obtain a premix;
[0067] (2) 85 parts by weight of POE, 10 parts by weight of PE, 5 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 35.5 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer mixer for 10 minutes, wherein the rheological temperature is 145°C and the rheological speed is 45 rpm; then the mixture is sent to a flat plate vulcanizer for continuous vulcanization at 5 MPa for 3 minutes, and then pressurized to 10 MPa for continuous vulcanization for 6 minutes; wherein the flat plate vulcanization temperature is 140°C, and then a 3kW LED ultraviolet light irradiation device is used in the molten state to directly carry out ultraviolet light irradiation cross-linking reaction for 15 minutes to prepare an insulating material for a 35KV cable.
[0068] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:1.8:10, ultrasonically dispersed for 30 minutes, stirred at 60°C and 400 r / min for 4 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0069] (Comparative Example 3)
[0070] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0071] 85 parts by mass of POE, 10 parts by mass of PE, 5 parts by mass of POE compatibilizer, 5 parts by mass of paraffin, 5 parts by mass of zinc oxide, 5 parts by mass of antioxidant, 5 parts by mass of stabilizer, 2 parts by mass of TAIC, 2.5 parts by mass of DCP, 35.5 parts by mass of aluminum hydroxide, and 60 parts by mass of modified kaolin were melt-blended in a torque rheometer internal mixer for 10 minutes, wherein the rheological temperature was 145°C and the rheological speed was 45 rpm; then they were sent to a flat-plate vulcanizer for continuous vulcanization at 5 MPa for 3 minutes, and then pressurized to 10 MPa for continuous vulcanization for 6 minutes; wherein the flat-plate vulcanization temperature was 140°C, and then a 3kW LED ultraviolet light irradiation device was used in a molten state to directly carry out ultraviolet light irradiation cross-linking reaction for 15 minutes to obtain an insulating material for a 35KV cable.
[0072] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:1.8:10, ultrasonically dispersed for 30 minutes, stirred at 60°C and 400 r / min for 4 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0073] (Comparative Example 4)
[0074] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0075] 85 parts by mass of POE, 10 parts by mass of PE, 5 parts by mass of POE compatibilizer, 5 parts by mass of paraffin, 5 parts by mass of zinc oxide, 5 parts by mass of antioxidant, 5 parts by mass of stabilizer, 2 parts by mass of TAIC, 2.5 parts by mass of DCP, 35.5 parts by mass of aluminum hydroxide, 60 parts by mass of modified kaolin, and 4.5 parts by mass of benzoic acid functionalized boron nitride were melt blended in a torque rheometer mixer for 10 minutes, wherein the rheological temperature was 145°C and the rheological speed was 45 rpm; then they were sent to a flat plate vulcanizer for continuous vulcanization at 5 MPa for 3 minutes, and then pressurized to 10 MPa for continuous vulcanization for 6 minutes; wherein the flat plate vulcanization temperature was 140°C, and then a 3kW LED ultraviolet light irradiation device was used in the molten state to directly carry out ultraviolet light irradiation cross-linking reaction for 15 minutes to obtain an insulating material for a 35KV cable.
[0076] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:1.8:10, ultrasonically dispersed for 30 minutes, stirred at 60°C and 400 r / min for 4 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0077] The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.95 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 5.55 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 45 minutes, and then the boron nitride dispersion is added, stirred for reaction for 4 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
[0078] (Example 5)
[0079] A method for preparing an insulating material for a 35KV cable comprises the following steps:
[0080] (1) 60 parts by weight of modified kaolin, 4.5 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate were mixed, stirred at 85° C. and 1000 r / min for 90 min, then poured into 1000 parts by weight of 10% sodium acetate solution and allowed to stand at room temperature for 4 h, followed by filtering, washing, and drying to obtain a premix;
[0081] (2) 85 parts by mass of POE, 10 parts by mass of PE, 5 parts by mass of POE compatibilizer, 5 parts by mass of paraffin, 5 parts by mass of zinc oxide, 5 parts by mass of antioxidant, 5 parts by mass of stabilizer, 2 parts by mass of TAIC, 2.5 parts by mass of DCP, 35.5 parts by mass of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer mixer for 10 minutes, wherein the rheological temperature is 145°C and the rheological speed is 45 rpm; then the mixture is sent to a plate vulcanizer and continuously vulcanized for 3 minutes at 5 MPa, and then pressurized to 10 MPa and continuously vulcanized for 6 minutes; wherein the plate vulcanization temperature is 140°C, and a 35KV cable insulation material is prepared.
[0082] The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed in a mass ratio of 1:1.8:10, ultrasonically dispersed for 30 minutes, stirred at 60°C and 400 r / min for 4 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
[0083] The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.95 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 5.55 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 45 minutes, and then the boron nitride dispersion is added, stirred for reaction for 4 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
[0084] Effect example
[0085] Table 1 below shows the performance test results of the 35KV cable insulation materials prepared in the embodiments of the present invention and the comparative examples:
[0086] Table 1
[0087]
[0088] It can be seen from Table 1 that the 35KV cable insulation materials prepared in Examples 1 to 3 have good electrical properties, mechanical properties and flame retardancy.
[0089] Compared with Example 2, Comparative Example 1 did not modify the kaolin, which also resulted in a large amount of kaolin agglomeration in the insulating material for 35KV cables, and the by-product benzopinacol could not be formed, resulting in decreased mechanical properties, flame retardant properties, and electrical properties.
[0090] Compared with Example 2, Comparative Example 2 did not perform functional modification on boron nitride, which also resulted in a large amount of agglomeration of boron nitride in the insulating material for 35KV cables, and the by-product benzopinacol could not be formed, resulting in decreased mechanical properties, flame retardant properties, and electrical properties.
[0091] Compared with Example 2, in Comparative Example 3, only aluminum hydroxide is used as the flame retardant, and the by-product benzopinacol cannot be formed, and the mechanical properties, flame retardant properties and electrical properties are reduced.
[0092] Compared with Example 2, in Comparative Example 4, the modified kaolin and benzoic acid-functionalized boron nitride were not mixed and reacted first, and the mechanical properties and electrical properties were reduced.
[0093] Compared with Example 2, Comparative Example 5 did not perform UV radiation crosslinking, and could not form the by-product benzopinacol, and the mechanical properties and electrical properties were reduced.
[0094] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An insulating material for 35KV cable, characterized in that: The raw material components, calculated by weight, include 75-100 parts by weight of POE, 0-10 parts by weight of PE, 0-5 parts by weight of POE compatibilizer, 20-60 parts by weight of modified kaolin, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, and 40 parts by weight of compound flame retardant.
2. The 35KV cable insulating material according to claim 1, characterized in that: The modified kaolin is obtained by modifying kaolin with styrene ethyl trimethoxy silane.
3. The 35KV cable insulating material according to claim 1, characterized in that: The compound flame retardant is obtained by compounding aluminum hydroxide and benzoic acid functionalized boron nitride.
4. The 35KV cable insulating material according to claim 3, characterized in that: The mass ratio of the aluminum hydroxide to the benzoic acid functionalized boron nitride is 35.5-38.5:1.5-4.
5.
5. A method for preparing an insulating material for a 35KV cable, characterized in that: The following steps are involved: (1) 20 to 60 parts by weight of modified kaolin, 1.5 to 4.5 parts by weight of benzoic acid functionalized boron nitride, and 22 parts by weight of boron trifluoride etherate are mixed, stirred and reacted at 84 to 86° C. for 80 to 100 minutes, then poured into 1000 parts by weight of a 10% sodium acetate solution and allowed to stand at room temperature for 3.5 to 4.5 hours, followed by filtering, washing, and drying to obtain a premix; (2) 75-100 parts by weight of POE, 0-10 parts by weight of PE, 0-5 parts by weight of POE compatibilizer, 5 parts by weight of paraffin, 5 parts by weight of zinc oxide, 5 parts by weight of antioxidant, 5 parts by weight of stabilizer, 2 parts by weight of TAIC, 2.5 parts by weight of DCP, 35.5-38.5 parts by weight of aluminum hydroxide, and the premix prepared in step (1) are melt-blended in a torque rheometer internal mixer for 8-12 minutes, then sent to a flat plate vulcanizer for flat plate vulcanization, and then directly subjected to ultraviolet irradiation cross-linking reaction in a molten state for 13-17 minutes to prepare an insulating material for a 35KV cable.
6. The method for preparing the 35KV cable insulating material according to claim 5, characterized in that: The preparation steps of the modified kaolin are as follows: kaolin, styrene ethyl trimethoxy silane and ethanol are mixed, ultrasonically dispersed for 25 to 35 minutes, stirred at 58 to 62° C. and a speed of 300 to 500 r / min for 3.5 to 4.5 hours, washed, dried, ground, and sieved through a 74 μm sieve to obtain modified kaolin.
7. The method for preparing the 35KV cable insulation material according to claim 6, characterized in that: The mass ratio of the kaolin, styrene ethyl trimethoxy silane and ethanol is 1:1.6-2:8-12.
8. The method for preparing the 35KV cable insulation material according to claim 5, characterized in that: The preparation steps of the benzoic acid functionalized boron nitride are as follows: under the protection of inert gas, 8 to 12 parts by mass of boron nitride are dispersed in 240 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 1.5 to 2.5 hours to obtain a boron nitride dispersion; 0.9 to 1 parts by mass of 4-aminobenzoic acid and 0.2 to 0.3 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.5 to 0.55 parts by mass of sodium nitrite and 5.5 to 6.5 parts by mass of a hydrochloric acid solution with a mass fraction of 20wt% are added, stirred for reaction for 40 to 50 minutes, and then the boron nitride dispersion is added, stirred for reaction for 3.5 to 4.5 hours, and then filtered, washed, and dried to obtain the benzoic acid functionalized boron nitride.
9. The method for preparing the 35KV cable insulation material according to claim 5, characterized in that: The rheological temperature of the torque rheometer internal mixer device is 140-150° C., and the rheological speed is 40-50 rpm.
10. The method for preparing the 35KV cable insulation material according to claim 5, characterized in that: The steps of the plate vulcanization are specifically as follows: firstly vulcanize continuously at 5 MPa for 2 to 4 minutes, and then pressurize to 10 MPa and vulcanize continuously for 4 to 8 minutes; wherein, the plate vulcanization temperature is 130 to 150°C.